Development of Edupreneurship for Elementary School Students through Assignments at Home - Firdania Dewi Soetrisno; Ihda A'yunil Khatimah; Andi Purnawan Putra (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2022)
This study aims to develop the attitudes, souls and abilities of elementary school students for entrepreneurship. Creative, innovative, independent, leadership, good at managing money, and having an unyielding spirit are some entrepreneurial attitudes that need to be instilled in children from an early age. This research uses a qualitative approach which is carried out by interviews, and documentation. The subjects of this study were second grade students of a Islamic Primate School in Banguntapan, Yogyakarta. The results of this study indicate that these entrepreneurial values become important points in the formation of life skills in children or students. In addition to education within the family, entrepreneurship education can be implemented in an integrated manner with learning activities at school through assignments at home.